PENYULUHAN MASYRAKAT TENTANG EDUKASI PROTOKOL KESEHATAN DI MASA ADAPTASI KEBIASAAN BARU - Ida Herdiani; Oni Sahroni; Usman Sasyari; Titin Suhartini; Ihsan Ihsan; Sania Maulida; Muhammad Dinnar; Ade Isna; Risti Supriatiningsih; Risma Siti Nurhamanah (Balarea: Jurnal Pengabdian Masyarakat, 2022)
The development of the covid-19 virus outbreak in a number of regions in Indonesia is very worrying for all levels of society, including its spread in the City of Tasikmalaya. In the context of preventing and controlling the virus, the government applies health protocols for the community in public places and facilities. The working area of the Tamansari Health Center is an area where the community is still less aware of complying with health protocols as evidenced by the large number of people who do not wear masks and crowd in public facilities. With these conditions, it will facilitate the transmission of the Covid-19 virus. By looking at these conditions, we will conduct education on health protocols during the adaptation period of new habits, which is the government's effort to break the chain of transmission of the Covid -19 virus.